Antifungal activity of etomidate against growing biofilms of fluconazole-resistant Candida spp. strains, binding to mannoproteins and molecular docking with the ALS3 protein. Issue 10 (7th October 2020) - Gurgel do Amaral Valente Sá, Lívia; da Silva, Cecília Rocha; Neto, João Batista de Andrade; do Nascimento, Francisca Bruna Stefany Aires; Barroso, Fátima Daiana Dias; da Silva, Lisandra Juvêncio; Cabral, Vitória Pessoa de Farias; Barbosa, Amanda Dias; Silva, Jacilene; Marinho, Emmanuel Silva; de Moraes, Manoel Odorico; Rios, Maria Erivanda França; et al.
Abstract : This study evaluated the effect of etomidate against biofilms of Candida spp. and analysed through molecular docking the interaction of this drug with ALS3, an important protein for fungal adhesion. Three fluconazole-resistant fungi were used: Candida albicans, Candida parapsilosis and Candida tropicalis . Growing biofilms were exposed to etomidate at 31.25–500 µg ml −1 . Then, an ALS3 adhesive protein from C. albicans was analysed through a molecular mapping technique, composed of a sequence of algorithms to perform molecular mapping simulation based on classic force field theory. Etomidate showed antifungal activity against growing biofilms of resistant C. albicans, C. parapsilosis and C. tropicalis at all concentrations used in the study. The etomidate coupling analysis revealed three interactions with the residues of interest compared to hepta-threonine, which remained at the ALS3 site. In addition, etomidate decreased the expression of mannoproteins on the surface of C. albicans . These results revealed that etomidate inhibited the growth of biofilms.